A New Quantitative Approach for Element-Mineral Determination Based on "EDS (Energy Dispersive Spectroscopy) Method". (29th August 2021) - Liu, Peigang; Wang, Zhelin; Zhang, Zhiqiang
Abstract : With the continuous development of hydrocarbon exploration, how to efficiently, economically, accurately, and comprehensively obtain mineral species, composition, and structure and diagenesis information has become one of the hot topics in both the academia and industry. By scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), a new method of qualitative mineral identification and quantitative measurement is established. Typical tight sandstone reservoir rock samples in the Ordos Basin are selected; through the element surface scanning image of "mineral element composition" and "pixel element combination", mineral types are distinguished, and mineral parameters such as types, characteristics, and content are rapidly and accurately determined. Meanwhile, such results achieved via the new method are compared with conventional XRD and TIMA methods. The results show that the new method exhibits several advantages: cost advantages compared to XRD experiment analysis technology and TIMA system and ability to analyze low content minerals which XRD techniques are hard to identify; it allows quantitative characterization on the phenomenon of mineral miscibility, which is of great significance to explore the mineral diagenetic evolution.